A Pediatric Acute Promyelocytic Leukemia With a Rare Karyotype of ider(17)(q10)t(15;17) and Favorable Outcome: A Case Report. Issue 41 (October 2015) - He, Yanli; Wang, Ping; Liang, Kaiwei; Chen, Xiangjun; Du, Wen; Li, Juan; Hu, Yanjie; Bai, Yan; Liu, Wei; Li, Xiaoqing; Jin, Runming; Zhang, Min; et al.
Abstract : Abstract: Acute promyelocytic leukemia (APL) is a specific malignant hematological disorder with a diagnostic hallmark of chromosome translocation t(15;17)(q22;q21). As a very rare secondary cytogenetic aberration in pediatric APL, ider(17q) (q10)t(15;17) was suggested to be a poor prognostic factor based on previous case reports. Here, we report a pediatric APL case with a rare karyotype of ider(17)(q10)t(15;17). Bone marrow aspiration, immunophenotyping, molecular biology, cytogenetic, and fluorescence in situ hybridization (FISH) analyses were performed at initial diagnosis and during the treatment. A 6-year-old boy was brought to our hospital with the chief complaint of bleeding gums twice and intermittent fever for 3 days in January 2013. He was diagnosed as low-risk APL according to the 2012 NCCN guideline on APL, with the expression of PML-RARA (bcr3 subtype) and the karyotype of 46, XY, der(15)t(15;17)(q22;q21), ider(17)(q10)t(15;17), which was further verified by FISH. The patient was treated through combination all-trans retinoic acid (ATRA) and arsenic with daunorubicin according to the 2012 NCCN guideline for APL. Continuous hematological completed remission (HCR) and major molecular remission (MMR) were achieved with normal karyotype for >28 months after induction chemotherapy. Different from previously reported cases, this pediatric APL patient with ider(17)(q10)t(15;17) displays favorable clinical outcomes, which might be related to the low-risk classification and arsenic treatment during the treatment. It suggests that ider(17)(q10)t(15;17) may not be the sole determinant for worse outcomes in pediatric APL and implies that more contributed factors should be considered for pediatric APL prognosis.